Doxycycline in Mitochondrial Mediated Pathway of Apoptosis: A Systematic Review - Sagar, Jayesh; Sales, Kevin; Seifalian, A.; Winslet, M. (Anti-Cancer Agents in Medicinal Chemistry, 2010)
Tetracyclines have been long known for their antimicrobial role. They are one of the most widely used antibiotics in clinical practice since last 5 decades. Recently their role as matrix metalloproteinase inhibitor and in apoptosis has widely attracted attention in biological field. Of them, doxycycline is one with long duration of actions and has recently been shown to have various anti-cancer properties, especially cytotoxic and anti-proliferative activities. Here, we systematically reviewed the role of doxycycline in the mitochondrial mediated apoptosis in various tissues. MEDLINE and EMBASE databases were searched using a formal search strategy with definite inclusion and exclusion criteria. Data extraction was performed for each included study using a custom designed data extraction form. A total of 81 references were identified through MEDLINE and 5 were identified through EMBASE. 74 references from MEDLINE and all 5 in EMBASE were excluded through reading titles, abstracts and full text. In total, 7 studies fulfilled inclusion criteria. Following systematic review of these studies, we concluded that doxycycline induces apoptosis through mitochondrial mediated pathway in different tissue cells however it may be cell specific. The caspase independent apoptosis as one of the mechanisms of actions of doxycycline needs further studies for better understanding.
Keywords: mitochondria